Comparative yield and nutritive value of forages from two cereal-legume based cropping systems. 2. Milk production and reproductive performance of crossbred dairy cows - Crosse, A.; Umunna, N.N.; Osuji, P.O.; Tegegne, Azage; Khalili, H.; Tedla, A. (1998)
Thirty-six crossbred cows were used in a 2 X 2 factorial arrangement in a randomized block design to evaluate forages from two cropping systems (1 and 2) and feeding levels (ad libitum, (Level1)) or 80 percent of ad libitum (Level 2) on milk yield, live weight, and reproductive performance. Crops in System 1 were: oat-vetch, wheat-trifolium, teff straw, and cowpea, and in System 2 maize-lablab replaced wheat-trifolium. The presence of legumes in crop mixtures improved forage quality. System X feeding level interaction effect was included in the analytical model. Mean (+ or - SE) daily milk yield was higher (P<0.01) in System 2 (4.02 (+ or -) 0.13 kg) than in System 1 (3.12 (+ or -) 0.13 kg) and higher in cows fed ad libitum (3.94 (+ or -) 0.14 kg, P<0.01) than in cows on the restricted regime (3.21 (+ or-). Milk composition was not influenced by treatments. Cows on Level 1 lost more (P<0.05) live weight than those on Level 2 (4.8 vs 1.8 percent) from mobilization of body reserves to support the increasing milk production. Conception rate was similar between systems but higher (P<0.05) for cows on Level 1 than Level 2. Supplementary feeding strategies for the type and level of feeding used, have to be developed in order to improve milk production and reproductive efficiency.